Implementation of Providing Alarm Clocks as Reminders to Take Medicine for TB Patients in Sukorambi Village, Sukorambi District, Jember Regency - Cahya Tribagus Hidayat; Suvi Murni; Alif Rizky Abdillah Pranata; Yesica Ajeng Dwi Rusti Arifin; Maretha Rezanastya; Intania; Angelica Shafabila Arsita (Cleanliness: Journal of Health Sciences and Medical Research, 2025)
Background: Tuberculosis is a disease caused by the bacillus Mycobacterium tuberculosis. This study aims to determine the effectiveness of providing an alarm clock as a reminder to take medicine for TB patients. By providing an alarm clock, it is expected that there will be no drug withdrawal incidents so that it can reduce the incidence of TBC in Sukorambi Village. Method: This study uses an observation method with a descriptive approach. Research Findings: In this study, the results of the study showed that the use of an alarm clock is very effective as a mediation to remind people to take medicine for TB patients. Consulsion: In this study, the results of the implementation of providing an alarm clock as a reminder to take medicine for TB patients are very effective.